The influence of feeding practice on the risk of stunting in infant and young children in developing countries:a literature review - Sri Melfa Damanik; Dessie Wanda (Ilmu Gizi Indonesia, 2019)
Bacground: Stunting is one of the conditions of failed to grow on the children where the child’s height is not obtained in accordance with the age of the child. There are a few things that become the main causes of stunting problem in children, as well as the ineffectiveness of child feeding practice. Objective: To find out the influence of feeding practice according to WHO guidelines on the risk of stunting in infant and young children in developing countries according on literature review. Methods: This literature review used search strategy on five databases involved Science Direct, EBSCOhost, ProQuest, Taylor & Franchis, and Scopus using the keywords of “stunting, feeding practice, infant and young children”. The author used several filter i.e. research articles, articles with English language, and published in 2008-2018. All articles were selected using Appraisal Tool of PRISMA and resulting 16 Articles. Results: Sixteen articles showed that minimum dietary diversity, exclusive breast feeding, the time of introduction of complementary feeding, high iron feeding, and frequency of feeding have a significant relationship with incident of stunting for infant and young children. Conclusion: The feeding practice for infant and young children in developing countries was not optimal. Providing education as early as possible to prospective mothers and mothers about proper feeding practices was expected can increase the knowledge and ability of mothers to practice appropriate feeding according to WHO recommendations.